2015
DOI: 10.1109/tsm.2015.2431375
|View full text |Cite
|
Sign up to set email alerts
|

Variability Improvement by Si Surface Flattening of Electrical Characteristics in MOSFETs With High-k HfON Gate Insulator

Abstract: Variability improvement of metal-oxidesemiconductor field-effect transistors (MOSFETs) characteristics with high-k HfON gate insulator by Si surface flattening was investigated. The Si surface flattening process was carried out by Ar/4.9%H2 anneal utilizing rapid thermal annealing (RTA) system. The HfON gate insulator was formed by the in-situ Ar/O2 plasma oxidation of HfN utilizing electron cyclotron resonance (ECR) plasma sputtering followed by the post deposition anneal (PDA) at 600 o C for 1 min. The Si su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…The Hf-based MONOS NVM was in situ formed on p-Si(100) substrate by the gate-last process. [22][23][24][25][26][27][28] After the active region formation and channel stop ion implantation, ion implantation was carried out for source and drain (S/D) regions (PH 3 , 5 × 10 15 cm −2 , 20 keV) followed by the activation annealing at 900 °C/20 min in N 2 ambient. Then, the MONOS structure was in situ deposited on p-Si(100) by electron cyclotron resonance plasma sputtering (AFTEX 3400) at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%
“…The Hf-based MONOS NVM was in situ formed on p-Si(100) substrate by the gate-last process. [22][23][24][25][26][27][28] After the active region formation and channel stop ion implantation, ion implantation was carried out for source and drain (S/D) regions (PH 3 , 5 × 10 15 cm −2 , 20 keV) followed by the activation annealing at 900 °C/20 min in N 2 ambient. Then, the MONOS structure was in situ deposited on p-Si(100) by electron cyclotron resonance plasma sputtering (AFTEX 3400) at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%
“…Conley等人 [28] [29] 研究认为高k介电材料的重离子硬击穿电压高于 超薄SiO 2 . Quinteros等人 [30] 和Singh等人 [31,32] 的实验 [37] 、三维FinFET器件 [38] 、U形沟道器件 [39] 、新 型高k栅介质器件 [40] 、非硅沟道器件 [6] 寻找新型高迁移率沟道材料以提升CMOS性能 是一个重要发展方向 [43,44] . GeSn具有很高的空穴迁 移率, 是新型纳米器件最有潜力的沟道材料之一 [45] , [45,46] , 但对其辐射效应研究国内外尚属空白.…”
Section: 重离子辐照对纳米器件材料的电学特性有较大unclassified
“…We have reported various Hf-based high-k gate insulators and also in-situ formation of HfN x (x < 1:0) gate electrode on the Hf-based high-k gate insulator [10,11,12,13,14]. It was found that the in-situ formation of HfN x (x < 1:0) gate electrode improved the electrical characteristics of Hf-based high-k gate insulator [13].…”
Section: Introductionmentioning
confidence: 97%